2016
DOI: 10.1007/s10539-016-9524-4
|View full text |Cite
|
Sign up to set email alerts
|

The phenotypic gambit: selective pressures and ESS methodology in evolutionary game theory

Abstract: The 'phenotypic gambit,' the assumption that we can ignore genetics and look at the fitness of phenotypes to determine the expected evolutionary dynamics of a population, is often used in evolutionary game theory. However, as this paper will show, an overlooked genotype to phenotype map can qualitatively affect evolution in ways the phenotypic approach cannot predict or explain. This gives us reason to believe that, even in the long-term, correspondences between phenotypic predictions and dynamical outcomes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Ignored causal influences range from molecular signaling pathways, to morphological structures, to nervous connections, to environmental context. Thus, the phenotypic gambit has significant limitations (Moore and Boake 1994;Golmulkiewicz 1998;Hadfield et al 2007;Rubin 2016), not the least of which is ignoring evolutionary dynamics on the way to an equilibrium (regardless of whether it is reached). It is perhaps ironic that behavior appears to be one of the least suited types of traits to study using this framework (Roff 1996;Fawcett et al 2013).…”
Section: Is Behavior Special?mentioning
confidence: 99%
“…Ignored causal influences range from molecular signaling pathways, to morphological structures, to nervous connections, to environmental context. Thus, the phenotypic gambit has significant limitations (Moore and Boake 1994;Golmulkiewicz 1998;Hadfield et al 2007;Rubin 2016), not the least of which is ignoring evolutionary dynamics on the way to an equilibrium (regardless of whether it is reached). It is perhaps ironic that behavior appears to be one of the least suited types of traits to study using this framework (Roff 1996;Fawcett et al 2013).…”
Section: Is Behavior Special?mentioning
confidence: 99%
“…Both of these problems have a shared cause; sensory drive relies on a phenotypic gambit approach to both trait and sensory system evolution. Such an approach assumes that evolution can create any phenotype and given “enough time” the model’s prediction will occur ( Rubin 2016 ). However, we now know that evolution can be constrained by molecular evolution both in the short term and over long periods of time ( Springer et al 2011 ).…”
Section: Light Detection By the Cone Cellsmentioning
confidence: 99%
“…The regression analyses presented in this study have shown that genetic correlation do not map directly to the phenotypic correlation, and overlooking genetic information (i.e. ) can qualitatively affect inferences (evolutionary, statistical, practical breeding outcomes) in ways a purely phenotypic approach cannot predict or explain (Rubin 2016, Kruuk et al 2008). Therefore, correspondences between phenotypic-based predictions on genetic outcomes are not robust for all plausible assumptions regarding the underlying genetics of traits (Hadfield et al 2007).…”
Section: Discussionmentioning
confidence: 76%